Public Satisfaction Analysis of Surabaya City Using Importance Performance Analysis and Customer Satisfaction Index - Putra, Fahmi Maulutfi Dwi; Ulama, Brodjol Sutijo Suprih (Jurnal Nasional Aplikasi Mekatronika, Otomasi dan Robot Industri (AMORI), 2024)
Service for the public is one of the tasks that the government must carry out. The government as a public servant must be able to provide services from all community needs in all matters such as licensing, population (Identity Card, Family Card, Birth Certificate) and so on. Surabaya City is one of the cities in East Java. Surabaya City has the task of handling regional autonomy affairs. The tasks carried out must be structurally and morally accountable to the community. In the service activities provided, there are still many complaints from the people of Surabaya City. Therefore, research was conducted on Surabaya City community satisfaction by directly surveying public services in order to increase Surabaya City community satisfaction. This research will be analysed using the customer satisfaction index and importance performance analysis methods so that it can be concluded that the people of Surabaya City are not satisfied with the public services provided.